2013
DOI: 10.1002/oby.20491
|View full text |Cite
|
Sign up to set email alerts
|

Obesity‐related dysregulation of the Tryptophan–Kynurenine metabolism: Role of age and parameters of the metabolic syndrome

Abstract: Objective: Obesity-related immune mediated systemic inflammation was associated with the development of the metabolic syndrome by induction of the tryptophan (TRP)-kynurenine (KYN) pathway. The study aimed to assess whether this holds true across the lifespan from juvenility to adulthood. Design and Methods: Five hundred twenty-seven participants aged between 10 and 65 years were analyzed. Standard anthropometric measures, carotid ultrasound, and laboratory analysis including interleukin-6, ultra-sensitive C-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(142 citation statements)
references
References 40 publications
9
111
1
3
Order By: Relevance
“…These findings are in line with current research and are possibly explained by chronic inflammation [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in line with current research and are possibly explained by chronic inflammation [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…PCA showed that altered plasma levels of AA and some of their metabolites, such as kynurenine (Kyn) and C5 acylcarnitine, are associated with many adiposity markers, as reported by other groups (3,24,33,42,44). One other study had examined associations between levels of glutamine, leucine, isoleucine, phenylalanine, and tyrosine and visceral obesity (25).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that ceramide concentrations are associated with insulin resistance (12,21,46). The ratio of kynurenine to tryptophan levels (Kyn/Trp), an increasingly recognized marker of inflammation and metabolic alterations, has been shown to be high in adult overweight or obese individuals (24,53), and also appears to be related to waist circumference independent of age (24).…”
mentioning
confidence: 99%
“…Interestingly, the recent finding that adipokines with potent anti-inflammatory properties (eg, adiponectin) have a role in the antidepressant effects of the NMDA receptor antagonist ketamine further supports the notion that inflammationinduced alterations of glutamatergic neurotransmission may contribute to the development of obesity-related depressive comorbidities (Machado-Vieira et al, 2016). Although activation of the kynurenine pathway has been primarily reported to represent a key component in the initiation and propagation of obesity and related medical complications, including CVD and the metabolic syndrome (Mangge et al, 2014), it is thus also possible that it contributes to the development of depressive comorbidities, notably through neurotoxic effects of kynurenine metabolites. The hippocampal atrophy found in obese subjects in comparison with healthy controls is in favor of this assumption (Fotuhi et al, 2012).…”
Section: Clinical and Experimental Evidencementioning
confidence: 99%